Minimally Invasive Surgery: Can We See Inside the Future - Elfaki, Elbagir Ali A.; Hamour, Osman A. (Gezira Journal of Health Sciences; Vol 8 No 1 (2012), 2012)
The substantial developments in surgery, over the last century with the advent of antiseptic substance, anesthetic agents, antibiotics, surgical nutrition, and organ transplantation, haven’t  changed neither the basic surgical tools nor the surgical techniques. Minimally invasive surgery (MIS), was first proposed by Wickham in 1986 because of the radical changes in the treatment of kidney stones between 1979 and 1983. This new concept of (MIS) has revolutionized the management of surgical disorders in a very short period of time.  It has moved the focus of surgery towards reducing the morbidity without compromising on the quality of healthcare (1) . (MIS) is getting in more and more in all fields of surgery, laparoscopic and endoscopic surgery are no exception (2) . It basically entailed entering the body cavities or lumina through the skin or through a natural orifice incurring the least damage to those organs or structures. . Collectively called minimal access surgery it has developed so much to the extent of being impossible to halt or withdraw it back. Recently computerized designing of laparoscopic instrument is introduced and microprocessor controlled safety features are added.  MIS has proved a boom for patients over the last 25 years. It has significantly reduced  hospital stay, grossly reduced the  patients’ recovery time, and greatly improved the cosmetic consequences of operations with less pain and  less strain of the organism. Despite the improvement in outcomes with laparoscopy, the technique still has some limitations.  Apart from grand cost and training needs, there is definite loss of tactile perception and of course the surgeon’s eyesight is limited by the two dimensional view (3) .